Developing of Ispring Quiz Maker as an Evaluation Media in the Pragmatics Course - Hima Roiku Dinia; Chadijah Qubro Lubis; Moh. Zawawi; Umi Machmudah; Miftahul Huda; Muhammad Hauzan Ariq Lubis (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research aimed to determining the suitability of iSpring Quiz Maker as an evaluation media in the Arabic Language and Literature pragmatics course at UIN Malang, understanding the response of students' interest in using iSpring Quiz Maker as an evaluation medium in the Arabic Language and Literature pragmatics course at UIN Malang, and knowing the effectiveness of using iSpring Quiz Maker as an evaluation medium in the Arabic Language and Literature pragmatics course at UIN Malang. The method used in this research is research and development (R & D) by applying the ADDIE model (analysis, design, development, implementation, and evaluation). The results of this research show: (1) iSpring Quiz Maker is declared very suitable for use as a medium for evaluating pragmatic courses based on the assessment of material expert validators and media expert validators; (2) Student responses are quite interested in using iSpring Quiz Maker as a medium for evaluating pragmatic courses; (3) iSpring Quiz Maker is effective as a pragmatic course evaluation medium because the percentage of the total number of students who get an exam score ≤ 50 is 26.3%, while the percentage of the total number of students who get an exam score > 50 is 73.7%.